2006
DOI: 10.1063/1.2347699
|View full text |Cite
|
Sign up to set email alerts
|

Confined alpha particle diagnostic system using an energetic He beam for ITER

Abstract: The beam neutralization system for measurement of the spatial and velocity distributions of alpha particles of ITER plasmas was studied. As forward angle detection against the beam injection direction is required for effective neutralization, arrangement of the measurement system using possible ports in ITER configuration is proposed. The count rate of neutralized alpha particles produced by the double charge exchange interaction with energetic He0 beam particles injected is estimated. The ratios of signal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…1 Sasao et al estimated the signal-to-noise ratio of He 0 obtained by double-charge-exchange reaction of alphas through injecting the energetic He 0 beam into ITER ͑Inter-national Thermonuclear Experimental Reactor͒. 2 The results indicated that a He − beam of 10 mA intensity and 1 -1.5 MeV energy are required to obtain enough signal of neutralized alphas against noise induced by fusion produced neutrons. The He 0 beam with ground electronic state is produced by spontaneous electron detachment from He − ions which are converted from He + ions with kinetic energy from 5 to 30 keV through a double-charge-exchange reaction with an alkali metal vapor in a small-aperture cell, and then that are accelerated up to MeV region.…”
Section: Introductionmentioning
confidence: 97%
“…1 Sasao et al estimated the signal-to-noise ratio of He 0 obtained by double-charge-exchange reaction of alphas through injecting the energetic He 0 beam into ITER ͑Inter-national Thermonuclear Experimental Reactor͒. 2 The results indicated that a He − beam of 10 mA intensity and 1 -1.5 MeV energy are required to obtain enough signal of neutralized alphas against noise induced by fusion produced neutrons. The He 0 beam with ground electronic state is produced by spontaneous electron detachment from He − ions which are converted from He + ions with kinetic energy from 5 to 30 keV through a double-charge-exchange reaction with an alkali metal vapor in a small-aperture cell, and then that are accelerated up to MeV region.…”
Section: Introductionmentioning
confidence: 97%
“…This ion beam system has many applications, including its use as a beam source for alpha particle measurements in ITER and its use in irradiation tests of materials [12]. High purity (∼99.95%) powder metallurgy (PM) tungsten specimens of 10 × 5 × 1 mm 3 were mounted at the focus point of the beam using a special specimen stage as shown in Fig.…”
Section: Beam Conditions and Setupsmentioning
confidence: 99%
“…The beam current was measured by a Rogowski coil. 7 It was also estimated as I beam = I acc − I dec , where I acc and I dec were the acceleration and deceleration current, and by a current onto a carbon beam dump target (100 × 100 × t2 mm 3 ). Agreement among these three measurements was satisfactorily good 7 when the vacuum level was good.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…We have been developing a 1-2 MeV He − beam of 10 mA region, because it is demanded for the production of an energetic ground state He 0 beam to diagnose the alpha particle confinement in a DT burning plasma of ITER. 2,3 The optimum beam energy for the He − production is in the range of 10-20 keV, therefore, the beam should be extracted at relatively low voltage. In addition, the beam should converge into a small size so that it passes through the charge exchange cell entrance and exit apertures, of typical size ranging 10-30 mm in diameter, in order to prevent the alkali vapor leakage.…”
Section: Introductionmentioning
confidence: 99%